2016
DOI: 10.1021/acs.jpcc.6b02198
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Polymers with Single-Wall Carbon Nanotubes

Abstract: Polymers are widely used for postsynthesis processing, purification, and individualization of single-wall carbon nanotubes (SWNTs) in aqueous or organic solvent environments. Here, the interaction of single-stranded DNA oligomers (ssDNA) and of a polyfluorene copolymer (F8T2) with (6,5) SWNTs was investigated from desorption kinetics and in the case of ssDNA also using adsorption isotherms. Eyring analysis of desorption rate constants reveals a linear increase of activation enthalpies with ssDNA oligomer lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 52 publications
2
31
0
1
Order By: Relevance
“…These results consistently suggest two interaction mechanisms of ssDNA and protein with SWCNTs: (i) (GT)15 ssDNA binds to SWCNTs with a higher affinity than (GT)6 ssDNA, thus reducing protein adsorption, and (ii) FBG interacts with ssDNA-SWCNTs more strongly than HSA. The former result agrees with prior work confirming that the rate of ssDNA desorption from SWCNTs decreases with increasing oligo length, 41 also valid in the presence of competing biomolecules. 8 As such, our data suggest that FBG protein adsorption leads to more significant ssDNA desorption from SWCNTs, whereas HSA adsorbs less strongly and accordingly causes less ssDNA desorption from SWCNTs.…”
Section: Multiplexed Fluorescence Tracking Enables Realtime Monitorinsupporting
confidence: 92%
“…These results consistently suggest two interaction mechanisms of ssDNA and protein with SWCNTs: (i) (GT)15 ssDNA binds to SWCNTs with a higher affinity than (GT)6 ssDNA, thus reducing protein adsorption, and (ii) FBG interacts with ssDNA-SWCNTs more strongly than HSA. The former result agrees with prior work confirming that the rate of ssDNA desorption from SWCNTs decreases with increasing oligo length, 41 also valid in the presence of competing biomolecules. 8 As such, our data suggest that FBG protein adsorption leads to more significant ssDNA desorption from SWCNTs, whereas HSA adsorbs less strongly and accordingly causes less ssDNA desorption from SWCNTs.…”
Section: Multiplexed Fluorescence Tracking Enables Realtime Monitorinsupporting
confidence: 92%
“…Im nächsten Schritt werden diese modifizierten DNA‐Sequenzen zur nicht‐kovalenten Umhüllung der SWCNT‐Oberfläche mittels Ultraschallbehandlung verwendet, was in einer kolloidal stabilen wässrigen SWCNT‐DNA‐Maleimid‐Lösung ( 3 ) resultiert. Nach Entfernung des überschüssigen DNA‐Maleimids ( 2 ) werden ≈5 Äquivalente (in Bezug auf die Anzahl der DNA‐Oligonukleotide auf der SWCNT‐Oberfläche) des reduzierten GFP‐bindenden Nanobodys zur Lösung von 3 hinzugefügt. Der Überschuss des GBP ( 4 ) wurde anhand von vorherigen Optimierungsexperimenten angepasst (siehe Abbildung S1/2).…”
Section: Figureunclassified
“…In an earlier work, we reported on a series of polyglycerol‐based amphiphiles to achieve efficient SWNT dispersion and individualization in water and showed that by altering the aromaticity of the suspension, we could alter the composition of the suspensions . The selective interaction between specific polymers and carbon nanotubes has been also shown to lead to chirality enrichment . In this work, we study the affinity of a polyglycerol‐based amphiphile toward nanotubes of a given chirality.…”
Section: Introductionmentioning
confidence: 98%